The Influence Mechanism of BIM on Green Building Engineering Project Management under the Background of Big Data - Ning Feng (Applied Bionics and Biomechanics)
The main framework of green construction management based on building information modeling (BIM) is constructed, and the related theories of BIM and green buildings are researched in more detail. The index of green construction is evaluated using the fuzzy evaluation method. The technical measures, management methods, field experience, and evaluation methods included in the green construction process are introduced in detail. Finally, effective measures to promote green construction management in China are proposed. This method is based on the specific technical measures and targeted management methods adopted in the green construction process. At the same time, the specific measures of construction project management in the era of big data are analyzed. It includes the collection and processing of data, the establishment of basic data models, the intelligent technology of big data clusters, and the application of blockchain big data. The purpose of the research is not only to effectively promote the development process of green construction in China, but also to reduce the waste of resources and environmental damage in the construction projects. At the same time, in the process of solving China’s environmental protection, building construction must follow the guiding suggestions put forward under the green construction. This has an important reference value for promoting China’s green construction work and has certain construction significance for realizing the sustainable development of the construction industry.